2021
DOI: 10.1038/s41598-021-86170-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid findings in patients with psychotic symptoms—a retrospective analysis

Abstract: In current international classification systems (ICD-10, DSM5), the diagnostic criteria for psychotic disorders (e.g. schizophrenia and schizoaffective disorder) are based on symptomatic descriptions since no unambiguous biomarkers are known to date. However, when underlying causes of psychotic symptoms, like inflammation, ischemia, or tumor affecting the neural tissue can be identified, a different classification is used ("psychotic disorder with delusions due to known physiological condition" (ICD-10: F06.2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
4
1
Order By: Relevance
“…More large-scale studies are therefore necessary to investigate any systematic age effect that might affect our findings. Surprisingly, we have also detected a higher proportion of patients with a paranoid hallucinatory syndrome in the group of psychiatric patients without neural autoantibodies as a tendency, a finding that contradicts previous reports on autoantibody-mediated psychosis in patients (18)(19)(20)(21) and animal models (10) and that might depend on cohort size; this result should be replicated in larger cohorts. Another limitation is that we did not systematically screen for any head injuries, none of the patients' clinical data suggested any trauma.…”
Section: Limitationscontrasting
confidence: 99%
“…More large-scale studies are therefore necessary to investigate any systematic age effect that might affect our findings. Surprisingly, we have also detected a higher proportion of patients with a paranoid hallucinatory syndrome in the group of psychiatric patients without neural autoantibodies as a tendency, a finding that contradicts previous reports on autoantibody-mediated psychosis in patients (18)(19)(20)(21) and animal models (10) and that might depend on cohort size; this result should be replicated in larger cohorts. Another limitation is that we did not systematically screen for any head injuries, none of the patients' clinical data suggested any trauma.…”
Section: Limitationscontrasting
confidence: 99%
“…Of these 39 bands, 9 were type II and 29 were type III bands, while one single band could not be classified to either of the categories. These rates are higher than those presented in the most recent meta-analysis [ 11 ] and other large-scale cohorts [ 12 , 26 ], but in line with one report from 2010 based on 61 cases [ 27 ]. Of note, the prevalence of OCBs type 2 and 3 among healthy subjects has been reported to be ~4% [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have reported CSF abnormalities in psychosis spectrum patients (e.g., elevated total protein concentration, and albumin ratio) [ 40 42 ] and we first aimed to replicate these findings. We therefore analyzed whether basic CSF parameters differed between F2x and IIH patients and added RRMS and NMDARE patients as unique inflammatory controls.…”
Section: Resultsmentioning
confidence: 85%